Mycotoxins in poultry production - Resanović Radmila M.; Nešić Ksenija D.; Nesić Vladimir D.; Palić Todor D.; Jaćević Vesna M. (Zbornik Matice Srpske za Prirodne Nauke, 2009)
All poultry is sensitive to mycotoxins. This partly depends on the type, age and production categories of poultry, their living conditions and nutritive status and partly on the type, quantity and duration of mycotoxin ingestion. The presence of mycotoxins results in significant health disorders and a decrease in production performances. This leads to considerable economic loss for the poultry industry - either direct losses, i.e. death of the poultry or the indirect ones, i.e. the decrease in body mass, number and quality of eggs, greater food conversion, and immunosuppression. Immunosuppression results in increased sensitivity to infective agents and a bad vaccinal response. Morevover, mycotoxin residues in poultry meat, eggs and products derived from them pose a threat to human health. In order to prevent and reduce the negative implications of mycotoxins in the poultry production, it is necessary to create both global and national strategies for combatting mycotoxins, advance diagnostic techniques and procedures, intensify the control of food quality, introduce new limits on the maximum amount of mycotoxins allowed in food and poultry feed used for certain species and categories of animals, and synchronise it with the European standards.